Path Planning of Three Wheeled Omni-Directional Robot Using Bezier Curve Tracing Technique and PID control Algorithm - Gavani, Madhukar; Tanpure, Dhananjay; Falake, Parasram (2019 IEEE Pune Section International Conference (PuneCon), 2019)
Nowadays, Drive types are getting popularized in the field of robotics. Holonomic Drive is the concept of existence of motion in every direction. Here, we have controlled the resulting vectors of motion of individual wheels of a three wheel omni robot that are ultimately responsible for a stabilized motion of the robot in any direction without changing the direction faced by the robot. It provides higher efficiency and controllability than non-holonomic drives, when used with odometry and PID control algorithms. Odometry basically is method of acquiring the real time positional data of a system in a world frame. PID control algorithm when applied on any system reduces the transient response and helps to acquire steady state conditions with less settling time.The purpose of this project is to create an algorithm for path planning of Three wheeled Omni Holonomic Drive. Here, we have successfully designed and implemented the algorithm called Bezier curve tracing technique for path planning using built-in encoders of motors and axis control of three wheel omni robot using PID, implemented using IMU(Inertial Measurement Unit).